Parents’ Communication with Teachers about Food and Nutrition Issues of Primary School Students - Gozde Aydin; Claire Margerison; Anthony Worsley; Alison Booth (Children, 2022)
Parents and teachers have a major influence in the formation of primary school children’s eating behaviours. Although the cooperation of parents and teachers has frequently been recommended in the promotion of healthy eating habits among primary school children, little is known about the communication between these two groups regarding food- and nutrition-related issues. This paper reports findings from semi-structured interviews with primary school parents (n = 19) and primary teachers (n = 17), as well as findings from a survey of 787 parents in Australia. Audio-recorded interviews were analysed using NVivo and descriptive statistics were calculated for the survey questions. The results indicated that their communications involved various topics, including allergies, lunchbox content, and supervision requests, through diverse communication channels. The risk of offending each other and time scarcity were reported as communication barriers. Parents mainly expected teachers to ensure that their children were given enough time to eat their lunch, teach healthy eating, and be good role models of healthy eating. This study highlights the need to overcome communication barriers between parents and teachers and support teachers in their multifaceted professional roles.